The Effect Of Tax Planning On Company Value With Financial Performance As Intervening Variables In Manufacturing Companies Registered In Indonesia Stock Exchange For 2014-2018 - Melisa Maharani; Sharifuddin Husen; Iman Sofian Suriawinata (Indonesian Journal of Business, Accounting and Management (IJBAM), 2020)
Abstract—This study aims to determine the effect of tax planning on firm value, and to determine the effect of tax planning on firm value with financial performance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. The research method used is a quantitative method using secondary data. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. Tax planning as an independent variable, firm value as the dependent variable, and financial performance as an intervening variable. The samples obtained were 25 companies with purposive sampling method. Descriptive statistical data analysis techniques using Stata 16 Software. The results of the study found that tax planning had a significant negative effect on firm value. A low CETR value will have a positive impact on firm value, on the contrary, if a large CETR value will have a negative impact on firm value. Meanwhile, CETR does not affect firm value through financial performance (ROA).